MiRNA a New Insight in Metabolic and Human Diseases: A Review : A New Insight into the Roles of MiRNAs - Jafri, Ibrahim (Cellular and Molecular Biology, 2023)
The purpose of this research is to examine existing studies on the association between microRNAs (miRNA) and age-related disorders. The miRNAs are small, noncoding RNA molecules with the ability to regulate gene expression. These are well-established in extracellular circulation, including various types of diseases such as cancer, cardiovascular diseases, and diabetes. Similarly, several miRNAs are associated with certain age-related conditions, such as increased miR-21 expression in cancer patients. Besides that, the miR-122 in atherosclerosis patients played an essential role in gene expression and disease. Therefore, the miRNA has the potential to serve as a reliable biomarker for the early detection, monitoring of progression, and regression of age-related diseases. To have a complete understanding of the mechanisms and the direct long-term effects that the miRNA has on the pathophysiology and development of diseases, additional research is required.